University teachers facing students with disabilities: Building bridges or erecting barriers? - Anabel Moriña Diez; Rosario López Gavira; Noelia Melero Aguilar; Mª Dolores Cortés Vega; Víctor Manuel Molina Romo (Universitat Politècnica de València, 2013)
The purpose of this article is to study, from the perspective of disabled students, how teachers may or may not contribute towards the integration of students at University through teacher's attitudes, teaching projects, curricular adaptations and development of tutorial action and training. The results of this work are part of a broader research project that is being carried out at the University of Seville2 . The overall goal of this project is to analyse the barriers and supports that students identify in their access, experience and results at University. Although the study takes into account both the institutional and the classroom perspective, in this article we only consider the figure of the university teacher, as far as identified barriers and supports in responding to disabled students are concerned.The biographical-narrative methodology has been applied for the development of this study, obtaining data through different techniques of information collection: groups of discussion, indepth interviews, observations in the classrooms, photographs, biograms, etc. The main obtained results are divided into the following blocks: (1) Attitudes of the teacher towards disabled students, (2) Inclusion and exclusion practices in the classroom, (3) curricular adaptations, (4) tutorials and (5) teacher training. The progress in the inclusive response to disabled students as a chance to improve university institutions is a highlighted idea among the conclusions of the article; thus universities should provide proactive answers rather than reactive ones.